Start-Up’s Road to Disruptive Innovation in the Digital Era: The Interplay Between Dynamic Capabilities and Business Model Innovation - Zhang, Ke; Feng, Lijie; Wang, Jinfeng; Qin, Guo; Li, Huailiang (Frontiers in Psychology, 2022)
The emergence and infusion of digital technologies bring greater chances for start-ups to conduct disruptive innovation through digital entrepreneurship. Despite the existed business practices, the happening mechanism of start-up’s disruptive innovation in the digital economy context remain unclear. This study aims to understand the evolutionary mechanism and fulfillment path start-ups' disruptive innovation in the digital era. The longitudinal case study is conducted for a Chinese Internet start-up that successfully launched disruptive innovation under the digital economy background. Adopting a process perspective, this study analyzes the evolutionary phases of digital disruptive innovation. Moreover, this study identifies the digital technologies adoption, dynamic capabilities deployment, and business model innovation as the key pillars, and their interactions. Finally, this study induces and proposes its evolution mechanism and fulfillment path models. This study enriches the research scope of disruptive innovation and digital entrepreneurship. This study can offer theoretical guidance for the start-ups' disruptive innovation in the digital era, and practical implications for implementing a digital catching-up strategy.